Synthesis and Biological Activities of New 1,2,3,4- Tetrahydroquinoline Derivatives Using Imino Diels-Alder Reaction - Mariam Abdul Jalil Abdul Razak1, Muhammad Abd Kadhum2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This research contains the preparation of some novel derivatives of tetrahydro quinolone. First step, includeprepared new Schiff’s bases compounds (I1-I5) were prepared by the direct condensation between diaminecompounds and aromatic aldehydes substituted by different groups. Tetrahydroquinoline derivativescompounds (I6-I10) were prepared through imino Diels-Alder reaction using the derivatives of Schiff basewith cinnamic acid, and Boron tri fluoride ethyl etherate (BF3.Et2O) as a catalyst. The prepared compoundswere identified by infrared spectra, 1H-NMR, and 13C-NMR. Antibacterial activity of the prepared compoundswas measured by using three pathogenic microorganisms including Staphyloccus haemolyticus, Klebsiellapneumonia,and Candida albicans. Also, a comparative study was achieved to study the biological activityof these prepared compounds using Agar Diffusion method.